The value of the botany archive of the University of Coimbra (Portugal) to biodiversity research, crowdsourcing and history of science projects. Issue 1 (January 2020) - da Silva, Ana Margarida Dias; Gonçalves, M. Teresa; Freitas, Helena; Gouveia, António Carmo
Abstract : This article highlights the value of the holdings of the Botany Archive of the University of Coimbra (BAUC) in the areas of natural sciences research, citizen science projects and science communication to general audiences. Inheritor of the records of activity of the Faculty of Natural Philosophy and the Botanic Garden of the University from 1772 onwards, BAUC now holds some 250 years of information, mostly originating from the nineteenth and twentieth centuries. It includes textual, iconographic, photographic and film information, from the Botanic Garden (held in part at the University Archive), the Botanic Institute, the Botany Museum (now integrated within the University Science Museum) and the University Herbarium. Much of this material is still unpublished but, in the twenty-first century, the BAUC is being reassessed via several projects. These include online databases (e.g. the "Digital Botanic Library and Archive"), the research project "The history of Botany in the University of Coimbra and its expression in the Portuguese-speaking world, " the documentary series "Tracking the Naturalists" and "Plant Letters", a participatory science initiative on the Zooinverse platform. All these projects demonstrate that BAUC offers the university community many opportunities for historical research and communication, and can yield new information when activated from contemporary perspectives.